Genetic variation in the kappa-casein gene (CSN3) of Chinese yak (Bos grunniens) and phylogenetic analysis of CSN3 sequences in the genus Bos - Prinzenberg, E.M.; Erhardt, G.; Han Jianlin (American Dairy Science Association, 2008)
Variants of kappa-casein (CSN3) have been extensively studied in cattle and 13 alleles have been identified at the protein and DNA levels to date. Evolution of some of these alleles and a possible common ancestor remain unclear. Polymerase chain reaction-single strand conformation polymorphism (PCR-SSCP) analysis of CSN3 exon IV in domesticated yak revealed a 2-allele polymorphism showing migration patterns different from known cattle variants. The PCR products of both yak CSN3 SSCP alleles were sequenced. All yak had nucleotide sequences coding for Thr in AA position 136 (identical to bovine CSN3*A) and Ala in position 148 (identical to bovine CSN3*B). The sequencing results were confirmed by PCR-RFLP analysis using HindIII and TaqI. A 12-bp insertion in the coding region, representing a repeated nucleotide and AA motif, was found in 1 yak allele. The duplication corresponds to the codons for AA 147 to 150 (Glu-Ala-Ser-Pro) or 148 to 151 (Ala-Ser-Pro-Glu), which are repeated identically. In 21 yak samples genotyped by PCR-SSCP analysis, frequencies for the insertion variant and the short variant were about 68 and 32%, respectively. The loss of the insertion may have led to the ancestral CSN3 allele from which all currently known variants of CSN3 in the genus Bos evolved. This is the first report of polymorphisms in the yak CSN3 gene and may be helpful for future studies on genetic variation within and between yak populations or on associated traits.